ANALISIS YURIDIS KEADAAN YANG MEMBERATKAN TERDAKWA PENGEDAR OBAT ABORSI SECARA ONLINE - Andre Suhada Ambarita; Davit Rahmadan; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The rise of online abortion drug dealers today is troubling the public because of their widecirculation due to the ease of creating websites or online advertisements. The abortion drugs areCytotec and Gastrul, hard drugs on the G list (gevaarlijk) which contain misoprostol. The persondistributing the drug should have the expertise and permit and those who obtain and use it musthave a doctor's prescription. Misoprostol is a drug for treating ulcers and unusual stomach ulcersas well as other diseases, but it is often misused for abortion which can cause various health hazardsto cause death to pregnant women and the fetus. In relation to law enforcement through courtdecisions, considerations of aggravating and mitigating circumstances must be included in thesentencing decision as referred to in Article 197 paragraph (1) letter F of the Criminal ProcedureCode (KUHAP) for the accused before the judge renders a sentencing decision. This considerationmust be clear and careful because it can affect the proportionality of the severity of the sentence.However, juridically there is no definition and assessment of this situation, even if one looks backon the objectives and guidelines for sentencing. In every consideration of the aggravatingcircumstances of the accused, online abortion drug dealers have differences in terms of endangeringhealth and disturbing the public. Therefore, the purpose of this thesis research is first, what is theideal consideration of the aggravating circumstances of the online abortion drug dealer and howdoes the inaccurate consideration of the aggravating and mitigating circumstances affect thedefendant in the sentencing decision.This type of research is normative juridical or literature study on secondary data, with a caseapproach, using qualitative analysis methods, then the authors draw conclusions deductively.From the results of the research problem there are two main things that can be concluded.First, considering the aggravating circumstances of defendants who sell abortion drugs online, theyshould consider that the actions of each defendant endanger the health of others and disturb thecommunity. Second, inaccurate consideration of the circumstances and aggravating the defendantcan affect the proportionality of the severity of the sentence. The author's suggestion in this researchis first that judges who try and decide criminal cases are always more careful and thorough inassessing the aggravating and mitigating circumstances of the defendant before imposing asentencing decision. Second, it is hoped that inaccurate considerations of aggravating andmitigating circumstances in the future can be minimized by looking at the two conditions in abalanced and intact manner.Keywords: Dealer-Abortion Drug-Misoprostol-Aggravating and Mitigating Circumstance